Developing Multicultural Religious Competence in Teachers through Reflective Seminars in Nigeria - Gift, Ozokoye C; Farjani , Mustafa (Al-Insyiroh: Jurnal Studi Keislaman, 2025)
This study explores the impact of a reflective-based seminar in enhancing religious Multicultural competencies among pre-service teachers in Nigeria. The purpose of the research is to examine whether a seminar focused on religious identity and interfaith dialogue can improve pre-service teachers' Cultural Competence and beliefs about fostering religious harmony in educational settings. A total of 70 pre-service teachers from various teacher training institutions in Nigeria participated in the study. The participants were divided into an intervention group, which attended a reflective seminar, and a control group that received traditional diversity training. The research used both quantitative and qualitative methods, with the intervention group showing significant improvements in Cultural Competence, attitudes towards religious diversity, and awareness of stereotypes. Qualitative findings also revealed that participants gained greater self-awareness, developed strategies for promoting inclusivity, and reported challenges in implementing the learned strategies in real-world classroom settings. The study concludes that reflective-based seminars are effective in enhancing religious multicultural competence among future educators, providing a practical framework for integrating such training into teacher education programs in Nigeria. These seminars can play a crucial role in shaping inclusive learning environments by equipping teachers with the skills necessary to manage religious diversity in the classroom, and offer valuable policy recommendations for improving teacher preparation in diverse educational contexts